2016
DOI: 10.1158/1535-7163.mct-15-0601
|View full text |Cite
|
Sign up to set email alerts
|

Mutated Pathways as a Guide to Adjuvant Therapy Treatments for Breast Cancer

Abstract: Adjuvant therapy following breast cancer surgery generally consists of either a course of chemotherapy if the cancer lacks hormone receptors, or a course of hormonal therapy, otherwise. Here we report a correlation between adjuvant strategy, and mutated pathway patterns. In particular we find that for breast cancer patients, pathways enriched in non-synonymous mutations in the chemotherapy group, are distinct from those of the hormonal therapy group. We apply a recently developed method that identifies collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Some studies have shown that TNN and USH2A can be used as the most common mutant genes with predictive effect on new antigens [41]. OBSCN mutation is closely related to breast cancer and colorectal cancer [42][43]. However, the role of these mutations in ovarian cancer is rarely discussed in existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that TNN and USH2A can be used as the most common mutant genes with predictive effect on new antigens [41]. OBSCN mutation is closely related to breast cancer and colorectal cancer [42][43]. However, the role of these mutations in ovarian cancer is rarely discussed in existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…OBSCN gene is frequently and consistently mutated in various cancers with a strong correlation with breast, colorectal and other female related cancers. Recent studies revealed that TP53 and OBSCN genes are highly mutated among 189 candidate genes in breast and colorectal cancers [ 13 , 17 ]. However, scientific background on OBSCN mutation and its impacts are limited in comparison to the other key genes involved in breast cancer [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%